Improving the quality of toll Road services to increase satisfaction level of Pekanbaru – Dumai toll road - Putra, Syah Gemma; Wicaksono, Agus Dwi; Prayitno, Gunawan; Hiep, Nguyen Trong (Civil and Environmental Science Journal (CIVENSE), 2023)
Pekanbaru - Dumai toll road is one of the segments of the Trans Sumatra toll roads built by PT Hutama Karya. The Pekanbaru - Dumai toll road connects economic centers in Riau Province, including Dumai-Duri-Kandis-Petapahan-Minas-Pekanbaru. On the Pekanbaru-Dumai toll road, problems with service quality were found. This research has two objectives: to analyze the quality of service and level of satisfaction of the toll road users assessed from the toll road users. The second objective is to formulate referral recommendations to fix and improve the quality of toll road services in terms of the needs and expectations of toll road users. This study employs IPA analysis to identify the degree of performance and the level of importance of service qualities, CSI analysis to determine the level of satisfaction of toll road users, and QFD analysis to define the development priorities for the Pekanbaru-Dumai toll road. The results of this study obtained that the satisfaction level of the Pekanbaru-Dumai toll road was 0.63, with the category quite satisfied. The priority is toll road surface maintenance regularly, the second priority is toll road lighting facility maintenance regularly, the third priority is toll road safety facility maintenance regularly, the fourth priority is to improve rest area facilities, the fifth priority is to expand parking in the rest area, and the absolute priority is to enforce electronic fines or (e-ticket) for traffic violations.